Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1002/jbm.820261006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface processing on the attachment, orientation, and proliferation of human gingival fibroblasts on titanium

Abstract: The adhesion, orientation, and proliferation of human gingival fibroblasts was studied on electropolished (elpTi), etched (etchTi), and sandblasted (sblTi) titanium surfaces. The texture, chemical state, and composition of the titanium surfaces were analyzed using a surface tracing instrument and electron spectroscopy for chemical analysis. Considerable differences were evident in the surface texture and chemical composition of the differently treated titanium plates. Electropolishing produced the smoothest an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(120 citation statements)
references
References 29 publications
6
108
0
2
Order By: Relevance
“…It is known that fibroblasts show greater affinity for smooth or finely grooved surfaces than for rough ones 22,23) . Our study confirmed this evidence as, after 3 h of culture, SEM observations did not reveal deep modifications in HGs morphology, other than in cells grown on CAD/CAM manufactured zirconia, with no additional surface treatment (Group A).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that fibroblasts show greater affinity for smooth or finely grooved surfaces than for rough ones 22,23) . Our study confirmed this evidence as, after 3 h of culture, SEM observations did not reveal deep modifications in HGs morphology, other than in cells grown on CAD/CAM manufactured zirconia, with no additional surface treatment (Group A).…”
Section: Discussionmentioning
confidence: 99%
“…roughness) on material surfaces are also crucial in cell and tissue responses to biomaterials. Indeed, surface roughness has shown to alter fibroblast proliferation on aluminiun, titanium and titanium alloys substrates [60][61][62] , and strongly influence bacterial attachment to nitinol, titanium and glass surfaces [63][64][65][66] . Overall, the three functionalization strategies displayed the same value of R a (~ 30 nm; Table 2), slightly increasing the original R a of control samples (~ 25 nm; Table 2).…”
Section: Physicochemical Characterization Of the Surfacesmentioning
confidence: 99%
“…13 However, researchers gradually discovered that the machined necks led to crestal bone loss during early functional loading after several decades of installation procedures. [14][15][16][17] Additionally, some scholars reported that the micro-roughened surface did not increase plaque accumulation, nor did it lead to crestal bone loss; however, the surface was reportedly more conducive for forming a wide and tightly attached closed loop of connective tissue.…”
mentioning
confidence: 99%